Antibacterial Activity of Mangosteen Leaf and Bark Fraction Against Salmonella spp Causes Diabetic Ulcers - Salmah Wilujeng Anggraini; Susanti Erikania; Vevi Maritha (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
Diabetes mellitus is a degenerative disease due to impaired cell function β-pancreas in insulin production causing hyperglycemics accompanied by microvascular complications such as diabetic ulcers. This condition is aggravated by bacterial contamination, one of which is Salmonella spp. The use of natural ingredients that have the potential for the treatment of diabetic ulcers is the mangosteen plant (Garcinia mangostana L.), so the identification of Salmonella spp in diabetic ulcers and testing the antibacterial activity of ethyl acetate and n-hexan leaves and mangosteen stem skins is carried out. The method started from the stage of bacterial identification using selective media, gram staining, biochemical testing, and antibacterial activity tests by diffusion of discs. Results showed that Salmonella spp was positif in SSA-specific media, biochemical tests, red bacteria, rod-shaped. Antibiotic sensitivity tests obtained by ciprofloxacin had the strongest activity of 30.20±1.37mm. The largest antibacterial activity result at a concentration of 100% obtained the ethyl acetate fraction of mangosteen leaves is 17.30±0.5mm compared to the fraction of n-hexane leaves of 8.81±0.32mm, ethyl acetate fraction and n-hexan mangosteen stem skin of 13.28±0.95mm, 7.42±0.45mm